Explorapp Cali: aplicación móvil sobre la cultura caleña para niños y niñas de 4 a 6 años - Gomez Zuluaga, Sebastian (Ingenierias, 2017)
This degree work was to develop a mobile application implementing it video books (with interactive functions stories) and augmented reality as a support tool for teaching evolution in the city of Cali in early childhood. For application development children from 4 to 6 years they were selected for being an age where their levels of learning and knowledge are emerging, and established itself as a central axis to use this application, as a support to strengthen recreationally process children learning independently and individually outside the classroom. They were conducted research and consultations to obtain the best possible source and specific, both in the educational and pedagogical area, as in the multimedia area, for greater effectiveness of the application. For the educational study, we took into account, psychologist, Piaget, Vygotsky and Bruner, which provide large bases in child education as the dimensions of child development, psychological instruments, in this case directed at children from 4 to 6 years and help generate a correct and stimulating learning.